RTK Kinematic Positioning Accuracy with Double Phase Difference of SIS GNSS Signals - Lucjan Setlak; Rafał Kowalik (Communications - Scientific letters of the University of Zilina, 2021)
The article presents results of verification of the kinematic measurements usefulness for precise real-time positioning RTK in the local reference system. These measurements allow for continuous RTK measurements in the event of temporary interruptions in radio or internet connections, which are the main reason for interruptions in RTK kinematic measurements and cause a decrease in the reliability and efficiency of this positioning method. Short interruptions communication are allowed during the loss of the key correction stream from the local RTK support network, so the global corrections obtained from the geostationary satellite are used. The aim of the article was to analyze the accuracy of measuring the position of moving objects. Practical conclusions were formulated according to the research subject, the presented mathematical models, the experiment and the analysis of the obtained results.